Regional Information System for Banana and Plantain for Asia and the Pacific (RISBAP): Proceedings of a consultation/workshop, 1-3 April 1996, Los Baños, Philippines - Valmayor, R.V.; Roa, V.N.; Cabangbang, V.F.; Regional Information System for Banana and Plantain for Asia and the Pacific (1996)
The RISBAP - Regional Information System for Banana and Plantain - Asia and the Pacific - objectives are the following: to promote information exchange among banana scientists, research administrators, and development workers in the region; to provide information services including regional collation of current and past banana research and development; to facilitate information exchange between the global INIBAP Info-Doc system and other regional information networks; and to provide training on information processing and database management. The RISBAP network will be composed of the RISBAP Center, the national centers representing each member country and institution, the RISBAP network advisory committee, and the users. Out of print